Subsidized health insurance impact among the poor: Evidence on out-of-pocket health expenditures in Indonesia - Sosodoro, Niken Larasati; Ramadhan, Rasi Tamadhika Fajar; Susamto, Akhmad Akbar (Jurnal Ekonomi & Studi Pembangunan, 2023)
Universal Health Care (UHC) in Indonesia, named the National Health Insurance (Jaminan Kesehatan Nasional - JKN), has been running since 2014. JKN was predicted to be the most extensive UHC program in the world. Under JKN, the poor get free health services through the cashless method through a sub-program called Contribution Assistance Recipients (Penerima Bantuan Iuran - PBI). Unfortunately, JKN faced several failures to cover the program's expenditures within years. Within the current dynamics, was PBI, as part of JKN still effectively helping the poor? We examined the effectiveness of the PBI program by measuring differences in out-of-pocket health expenditures for the poor with similar socio-economic characteristics who used PBI and those who did not. We incorporated secondary data from National Socio-economic Survey (SUSENAS). The dataset was executed by using Propensity Score Matching (PSM) methodology. We used health expenditures and socio-economic parameters such as income, education, and gender from the 2017 and 2018 SUSENAS data. We found that in 2017, the total health expenditures of the PBI beneficiaries were lower than the non-beneficiaries. Nevertheless, by merging all two years' data, similar to 2018, we found general pattern that PBI participants' total health out-of-pocket payments were bigger than the non-participants. Health expenditures such as medicine, traditional practitioners, and others, were expenditure classifications in which PBI beneficiaries had lower expenses than non-beneficiaries in 2017. Therefore, Therefore, the UHC subsidy program for the poor in Indonesia has not only been ineffective through the years of implementation but also has not been effectively implemented for all variations of health expenditure types.